Covid-19. Some moments of the 21st century, with a look at Milan - Roberto Busi (TeMA: Journal of Land Use, Mobility and Environment, 2020)
Critically narrating some impacts on the civitas and urbs of the pandemic, the paper argues how the relative pathos of death and poverty unleashed on Milan is, in fact, a contingency on the endless flux of the urban body in the long history of the city. The text, divided into five paragraphs - then (May 2019), yesterday (March 2020), today (April 2020), tomorrow (May 2020) and later (May 2030) -, in addition to the bibliography, develops as in a Gaussian curve, the two extremes being (“then” and “later”) in points before and after the beginning of the curvature, respectively (i.e., describing situations “at full throttle”), the centre (“today”) the peak of the curve and the two intermediates (“yesterday” and “tomorrow”) in its ascending and descending sections, respectively. The style varies from calmness at the extremes (with mainly hypotactic periods) to the unease of the intermediates, namely, at its peak (with mainly paratactic periods).